Elementos da cibercultura e suportes performanciais em 2 ou + corpos no mesmo espaço, de Arnaldo Antunes - (:unkn) unknown (Universidade Federal do Amazonas, 2014)
This paper discusses, in general terms, some aspects of the multimedia art of the poet Arnaldo Antunes, focusing in more detail, in some considerations on 2 ou + corpos no mesmo espaço, a book published in 2009 by the publisher Perspective. In general terms, relates to the procedural aspects of this poetry to theories pf Pierre Lèvy on which concerns the cyberculture; and Esther Langdon and Paul Zumthor, around the performance of poetic and indexical reading, conjugated to understanding Diana Domingues around the humanization of technologies. Specifically, refers to the study of four poems in the book: "agá", "mundo cão", "meu tempo" and "agouro". In the first three poems, presents a distinct study, considering the different media of communication thereof : written version (book) and performative version (offline ), voiced and recorded on CD. In the case of the poem "agouro" is analyzed only in its written version (book). The study, a generalized way, assumes that these poems to be published in different communication media and, moreover, remain in cyberspace for it´s own publication, which promotes a way of approaching life with poetry.
Keywords: Poesia; Arnaldo Antunes; Performace; Ciberespaço; Poetry; Ciberspace; LINGUÍSTICA, LETRAS E ARTES: LETRAS